Optimization study of coupled vane compressor - Hing, Joel Zi Long (Nanyang Technological University, 2022)
In agriculture, manufacturing, pharmaceuticals, food and beverage as well as in our daily lives, compressors are useful because it pressurizes fluid which can then be harvested for use in powering tools and machinery in these industries. Due to this the competition to develop compressors with better performance as well as being compact is extremely competitive. This combined with the current environmental issues, the race to develop compressors that are energy efficiency and compact is a tough one. With this in mind, Dr Pradeep Shakya and Professor Ooi Kim Tiow designed the CVC compressor to have higher mechanical efficiency and volumetric capacity than other rotary compressors currently available. In this report, an optimization algorithm called the Box’s complex method linked with the CVC simulation program in order to carry out optimization of the geometric properties of the CVC. 7 design variables will be used namely, the cylinder radius, rotor to cylinder ratio, vane thickness, suction port diameter, discharge port diameter, valve thickness and valve length. The main goal is to obtain a set of geometric parameters that would yield the highest mechanical efficiency, volumetric efficiency and COP possible. A detailed documentation of the mathematical model used as well as the design of the optimization problem will be provided in this report.